Dynamics of International Business: Asia-Pacific Business Cases - Ramburuth, Prem; Stringer, Christina; Serapio, Manuel (Cambridge : Cambridge University Press, 2013)
Dynamics of International Business: Asia-Pacific Business Cases brings the challenges and complexities of the contemporary international business environment into the classroom. These authentic case studies, based on recent research and events, enable students to engage with the economic, social, political and intercultural factors that impact on international business and understand how these factors are addressed in the real world.Designed to facilitate a problem-based learning approach, the cases in this book: draw on a diverse range of businesses and industries - from seafood to video games to renewable energy illustrate fundamental themes and concerns within global business, including ethics, sustainability, emerging markets and cultural and legal differences span many countries across the Asia-Pacific region include discussion questions that encourage students to apply international business theory in the context of realistic scenarios include references and suggestions for further reading. Extra resources for instructors, including case synopses and learning objectives, are available on the companion website at www.cambridge.edu.au/academic/internationalbusiness.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: International business enterprises; Australian